Electrocardiographic characteristics in individuals with cocaine use disorder. (1st March 2017) - Mahoney, James J.; Haile, Colin N.; De La Garza, Richard; Thakkar, Harsh; Newton, Thomas F.
Abstract : Background and Objectives: Chronic cocaine use has been linked to several abnormalities in cardiac functioning. The objective of this study was to further characterize baseline heart rate and electrocardiograph (ECG) profiles of individuals with cocaine use disorder (CUD) by evaluating demographic and drug use variables that may impact cardiovascular profiles. Methods: Participants with CUD ( n  = 335, primarily African‐American males) provided demographic and drug use data and ECG profiles (eg, heart rate, PR Interval, QRS, and QTc) were obtained via 12‐lead ECG. Results: Forty‐eight percent and ten percent of cocaine users met criteria for sinus bradycardia (heart rate ≤60) and severe bradycardia (heart rate ≤50), respectively. Females had significantly higher heart rate ( p  = .020, d  = .30) and QTc ( p  < .001, d  = .75) and significantly lower QRS ( p  = .002, d  = .42) in comparison to males. Those who were cocaine positive had higher QTc ( p  = .025, d  = .26) with a higher prevalence of bradycardia (chi‐square = 3.91, p  = .048) than those who were negative. Cocaine users who also used alcohol had significantly lower PR Interval ( p  = .003, d  = .36), QRS ( p  = .014, d  = .29), and QTc ( p  = .037, d  = .25) than those who denied alcohol use. Conclusions: These findings characterize the baseline heart rate and ECG profiles of individuals with CUD, confirm previous reports of cocaine‐induced alterations in cardiovascular function, and demonstrate factors impacting cardiovascular profiles. Scientific Significance: While exploratory, these results suggest the presence of bradycardia may serve as a useful biomarker for initiating therapy for individuals with CUD and averting potential adverse cardiovascular events. Future prospective studies are needed to assess this possibility. (Am J Addict 2017;26:221–227)